High Incidence of Severe Erectile Dysfunction in Benign Prostatic Hyperplasia Patients - Zuhirman; Nur Rasyid; Yanwirasti (International Journal of Medical Research, 2014)
Introduction: Erectile Dysfunction (ED) and Benign Prostate Hypertrophy (BPH) are two health-related problems which are experienced by men aged over forty years. BPH and ED highly affect a man’s quality of life (QoL). It is necessary to conduct research on the correlations between BPH and ED by using two kinds of valid scores, i.e. the International Prostate Symptoms Scores (IPSS) to determine the severity of BPH and the International Index of Erectile Function-5 (IIEF-5) to screen the existence of ED in BPH patients. Objectives: The aim of this study is to identify the symptoms of BPH patients with ED and the correlations between ED and BPH by using IPSS, IIEF-5 and QoL. Materials and Methods: This is a cross-sectional study which analyzes correlations between the severity of BPH and the severity ED by using IPSS and IIEF-5 in the Urology Clinic of Arifin Achmad Regional General Hospital. Results: Sixty (60) subjects fulfilled the inclusion criteria. The highest incidence of ED is present in BPH patients in the age group of 60-69 years (38.3%). In this group, 90% of all BPH patients were diagnosed with ED. The degree of BPH and ED experienced by these patients are also mostly severe, namely 53.3% and 40% respectively. The QoL scores are also mostly unsatisfied (58.3%) with the Spearman test also showing that significant and strong correlations do exist between the severities of BPH and ED (r = 0.836, p<0.001). Accordingly, a high incidence of ED on BPH patients is found and there are close correlations between the severities of BPH and ED, whereby if the severity of BPH increases, then the severity of ED will increase as well. Conclusion: Due to a high incidence of ED in BPH patients, we need to be able to detect the occurrence of ED in BPH patients earlier so as to manage ED at an earlier stage.